Antiviral Properties of Aqueous and Ethanol Extracts of Shaggy Mane (Coprinus comatus) Against Influenza Virus in in vitro and in vivo Experiments - E. I. Filippova; O. Yu. Mazurkov; I. A. Gorbunova; N. E. Kostina; N. A. Mazurkova (Антибиотики и Химиотерапия, 2020)
The chemical composition and anti-influenza activity of aqueous and ethanol extracts obtained from fruit bodies of Coprinus comatus (O.F. Müll.) Pers. (Shaggy mane) were studied. The antiviral activity of both mushroom extracts against influenza virus A/Aichi/2/68(H3N2) and A/chicken/Kurgan/05/2005(H5N1) was revealed for continuous culture of MDCK cells (index suppression of reproduction in the cells of both strains was from 2,0 to 4,7 lg). Dose dependency of antiviral activity of mushroom extracts was shown in in vitro experiments. The significant protective effect of both Coprinus comatus extracts on the influence on the survival rate of mice infected with influenza virus A/H3N2 in the treatment and prevention scheme was revealed in in vivo experiments.